1996
DOI: 10.1007/bf00838638
|View full text |Cite
|
Sign up to set email alerts
|

Changes in ventilation related to changes in electromyograph activity during repetitive bouts of isometric exercise in simulated sailing

Abstract: This study examined the control of ventilation during repetitive bouts of isometric exercise in simulated sailing. Eight male sailors completed four successive 3-min bouts of similar isometric effort on a dinghy simulator; bouts were separated by 15-s rest intervals. Quadriceps muscle integrated electromyograph activity (iEMG) was recorded during each bout and expressed as a percentage of activity during maximal voluntary contraction (%iEMGmax). From the first to the fourth bout, the 3-min mean averages for ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 26 publications
5
30
1
Order By: Relevance
“…Consequently, the [La b ] values may be related to the specific isometric effort component which characterizes the kitesurfing position. In the present study, the [La b ] responses are in good agreement with those reported in dinghy sailing during which [La b ] values hardly exceed 3 mmol l -1 either on water or in the laboratory, suggesting a limited oxygen deficit (e.g., Vogiatzis et al 1995Vogiatzis et al , 1996. Within this framework, Spurway (2007) recently indicated that the prolonged isometric effort resulted in a large increase in blood pressure and HR commonly accompanied by low or moderate increments in _ VO 2 and [La b ] responses.…”
Section: Discussionsupporting
confidence: 87%
“…Consequently, the [La b ] values may be related to the specific isometric effort component which characterizes the kitesurfing position. In the present study, the [La b ] responses are in good agreement with those reported in dinghy sailing during which [La b ] values hardly exceed 3 mmol l -1 either on water or in the laboratory, suggesting a limited oxygen deficit (e.g., Vogiatzis et al 1995Vogiatzis et al , 1996. Within this framework, Spurway (2007) recently indicated that the prolonged isometric effort resulted in a large increase in blood pressure and HR commonly accompanied by low or moderate increments in _ VO 2 and [La b ] responses.…”
Section: Discussionsupporting
confidence: 87%
“…The main factors are probably``a decrease in muscle pH and elevated extracellular potassium concentration'' as stated by Vogiatzis et al (1996). The fall in muscle pH causing inhibition in metabolic regulation as well as a decrease in the excitability of the muscle cell leads to a decrease in the mechanical eect of the contraction.…”
Section: A1mentioning
confidence: 99%
“…Moreover, the variations in [K + ] themselves represent a stimulus. The cellular variations in [K + ] stimulate muscular chemosensitive groups III and IV nerve ®bres, and similarly have been shown to take part in ventilation regulation (Vogiatzis et al 1996). It has been suggested that this action is probably strengthened by the stimulation of arterial chemoreceptors (Paterson and Nye 1991 Busse et al (1991).…”
Section: A1mentioning
confidence: 99%
“…Physiology (1996) 491T.P stimulation has, however, been proposed to account for the recurrence of hyperventilation reported to occur early in the recovery; this was associated with decreasing arterial pH and could be attributed to release of metabolic products from previously underperfused muscle (Poole et al 1988). We have reported a comparable pattern on cessation of isometric exercise in simulated dinghy sailing (Vogiatzis et al 1995). If such stimuli were acting at the arterial chemoreceptors, the response should be abolished or delayed in hyperoxia.…”
mentioning
confidence: 57%